1981
DOI: 10.1007/bf02402791
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hardness and microstructure in unoriented lamellar polyethylene

Abstract: The local deformation of the lamellar microstructure of isothermally melted crystallized u noriented polyethylene has been investigated using microindentation hardness (MH). The polymer can be visualized as a composite material consisting of hard and weak elements. The former, the lamellae, are considered to consist of mosaic blocks with liquidlike lattice distortions (paracrystallites). The latter are the interlamellar "amorphous" regions and the mosaic block lateral grain boundaries. The deformation mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 44 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…48 It is a measure of the local resistance of the material against the indenter penetration and is connected with the local irreversible deformation. Figure 6 shows the Vickers hardness of the samples as a function of Al 2 O 3 concentration on PVC.…”
Section: Resultsmentioning
confidence: 99%
“…48 It is a measure of the local resistance of the material against the indenter penetration and is connected with the local irreversible deformation. Figure 6 shows the Vickers hardness of the samples as a function of Al 2 O 3 concentration on PVC.…”
Section: Resultsmentioning
confidence: 99%
“…The energy per defect (14-16 Kcal/mol) derived from the slope of the plot for X < 0.025 is in accordance with the range of values derived from the analysis of equilibrium data in Figure 2. However, owing to the rapid quenching of these samples to low temperature, a larger inclusion of defects within the crystals than in the equilibrium crystallization experiments might be here involved [5]. Since only a minor fraction of the total number of branches are penetrating the crystals, the majority of these chain irregularities ought to be located at the interlamellar regions, on the crystal surface and within the lateral grain boundaries [2,30].…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of PE to fuming nitric acid after long exposures times has confirmed the level of defects remaining in the crystalline cores, using infrared spectroscopy [4]. It has, further, been shown that crystallization conditions may selectively affect the penetration of defects within the crystal lattice [5].…”
Section: Introductionmentioning
confidence: 96%
“…MHV and MHT, determined for a load of 40 g, the values of the parameter n and the microhardness of the crystal phase (MHV c ), calculated by the parallel model, 38 are listed in Table III. The parameter n, obtained from the slope of Mayer s lines has a value around 2, which means that MHVcan be considered as Comparing the graphs for the three samples it could be seen that MHV increases with increasing the degree of crystallinity and decreasing the molecular weight.…”
Section: Microhardness Measurementsmentioning
confidence: 99%